End-Of-Life Care in Dementia among Asian, A Scoping Review - Zulkernain, Firzanah Adabiah; Solehan, Hana Maizuliana; Sharil, Nor Safiqah; Marwan, Abdul Aziz; Faisal, Ummu Aiman; Mahamad, Ummi Affah (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Dementia is a neurocognitive disease characterised by a progressive deterioration of brain cognitive function. Dementia in the advanced stage should be treated as other terminal diseases. However, there is still a lack of acknowledgement regarding the end-of-life (EOL) care of people with dementia in Asian populations. This study aims to elucidate the components of EOL care in advanced dementia from the Asian perspective. MATERIAL AND METHODS: Arksey and O’Malley’s scoping review methodology framework was used to guide and conduct this scoping review. Databases of Pubmed, EBSCOhost, and Ovid Scholars were systematically searched using MeSH heading of end-of-life, palliative, dementia, and individual name of Asian countries. RESULT: Fourteen articles met the inclusion criteria. The majority of the studies involved interviews or questionnaires to the caregivers, the patients, and the healthcare professionals. The studies were done mostly in Taiwan and Japan and one from Indonesia. The studies reported themes that were categorised into life sustenance treatments and medications, advanced directives, the burden of the caretakers, and the knowledge, attitude, and practice of the healthcare providers or the family members. CONCLUSION: Major barriers in delivering EOL care to advanced dementia patients include knowledge, skills, communication, attitude, and beliefs, especially among developing countries in Asia. More education and awareness are needed amongst the healthcare providers and the public regarding this matter to ensure proper EOL care in advanced dementia patients.